Incidence, Characteristics and Outcomes of Large Vessel Stroke in COVID-19 Cohort: An International Multicenter Study. Issue 1 (18th March 2021) - Khandelwal, Priyank; Al-Mufti, Fawaz; Tiwari, Ambooj; Singla, Amit; Dmytriw, Adam A; Piano, Mariangela; Quilici, Luca; Pero, Guglielmo; Renieri, Leonardo; Limbucci, Nicola; Martínez-Galdámez, Mario; Schüller-Arteaga, Miguel; et al.
Abstract: BACKGROUND: While there are reports of acute ischemic stroke (AIS) in coronavirus disease 2019 (COVID-19) patients, the overall incidence of AIS and clinical characteristics of large vessel occlusion (LVO) remain unclear. OBJECTIVE: To attempt to establish incidence of AIS in COVID-19 patients in an international cohort. METHODS: A cross-sectional retrospective, multicenter study of consecutive patients admitted with AIS and COVID-19 was undertaken from March 1 to May 1, 2020 at 12 stroke centers from 4 countries. Out of those 12 centers, 9 centers admitted all types of strokes and data from those were used to calculate the incidence rate of AIS. Three centers exclusively transferred LVO stroke (LVOs) patients and were excluded only for the purposes of calculating the incidence of AIS. Detailed data were collected on consecutive LVOs in hospitalized patients who underwent mechanical thrombectomy (MT) across all 12 centers. RESULTS: Out of 6698 COVID-19 patients admitted to 9 stroke centers, the incidence of stroke was found to be 1.3% (interquartile range [IQR] 0.75%-1.7%). The median age of LVOs patients was 51 yr (IQR 50-75 yr), and in the US centers, African Americans comprised 28% of patients. Out of 66 LVOs, 10 patients (16%) were less than 50 yr of age. Among the LVOs eligible for MT, the average time from symptom onset to presentation was 558 min (IQR 82-695 min). A total of 21 (50%) patients were either discharged to home or discharged to acute rehabilitation facilities. CONCLUSION: LVO was predominant in patients with AIS and COVID-19 across 2 continents, occurring at a significantly younger age and affecting African Americans disproportionately in the USA. Graphical Abstract: